Visual expertise as embodied practice - Ivarsson, Jonas (Frontline Learning Research, 2017)
This study looks at the practice of thoracic radiology and follows a group of radiologists and radiophysicists in their efforts to find, discuss, and formulate issues or troubles ensuing the implementation of a new radiographic imaging technology. Based in the theoretical tradition of ethnomethodology it examines the local endogenous practices pertaining to the radiologists’ expertise in the interpretation of visual representations and tries to explicate the ways in which they draw upon various resources in order to accomplish their professional tasks. As the study is addressing the topic of visual expertise it also aims to do so in terms that acknowledge that all expertise is rooted in embodied practices. The analysis follows a case of what is called the enacted production of radiological reasoning. One of the central features of the described work is the manner in which it is carried out by way of the living present body of an expert. The experienced radiologist interweaves anatomical and technological terminology with visual representations and gestures in such a way that none of these components can be said to be superfluous to the argumentation. As a consequence, we should appreciate gestures and embodied actions as important means through which expertise become organised. These are parts of a repertoire of methods through which the experts learn their profession. In addition, gestures can also become enrolled in the re-negotiation of expertise in the face of new challenges.